2015
DOI: 10.1016/j.sjopt.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab in congenital retinal macrovessel with retinal arteriolar macroaneurysm

Abstract: Congenital retinal macrovessel (CRM) refers to an aberrant vessel, usually a vein, which traverses the macula and supplies both sides of the horizontal raphe. It is a rare condition, mostly asymptomatic and discovered on routine examination. We describe a case of both arterial and venous CRM with a macroaneurysm along the arterial CRM that presented with decreased vision due to prominent lipid exudation at the macula. Treatment with intravitreal bevacizumab resulted in a favourable anatomical as well as functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“… 1 This phenomenon was first described by Mauthner 2 in 1869, and the condition is most often an incidental finding. CRMs are rare, 3 but they have been observed in conjunction with several other ocular pathologies including branch retinal artery occlusion, 4 cavernous hemangioma, 5 macroaneurysm, 6 retinal detachment, 7 telangiectasias, 8 vitreous hemorrhage, 9 and reduced visual acuity due to obscuration of the fovea. 10 CRMs have previously been examined using fluorescein angiography, 3 , 11 but optical coherence tomography angiography (OCTA) now allows for noninvasive imaging of retinal vasculature and segmentation of the superficial and deep vascular layers.…”
Section: Introductionmentioning
confidence: 99%
“… 1 This phenomenon was first described by Mauthner 2 in 1869, and the condition is most often an incidental finding. CRMs are rare, 3 but they have been observed in conjunction with several other ocular pathologies including branch retinal artery occlusion, 4 cavernous hemangioma, 5 macroaneurysm, 6 retinal detachment, 7 telangiectasias, 8 vitreous hemorrhage, 9 and reduced visual acuity due to obscuration of the fovea. 10 CRMs have previously been examined using fluorescein angiography, 3 , 11 but optical coherence tomography angiography (OCTA) now allows for noninvasive imaging of retinal vasculature and segmentation of the superficial and deep vascular layers.…”
Section: Introductionmentioning
confidence: 99%
“…Because the majority of sufferers are asymptomatic, congenital retinal macrovessel is usually discovered unexpectedly on physical examinations or in patients with other ophthalmic diseases. In many studies and in normal eyes [6], partial congenital retinal macrovessel can be accompanied by branch retinal artery occlusion [7], retinal deep capillary ischaemia [8], macular retinal cavernous haemangioma [9], retinal arteriolar macroaneurysm [10,11], retinal peripheral telangiectasia [12], vitreous haemorrhage [13], retinal detachment [14], and even venous malformations of the brain [15]. Archer suggested that retinal arteriovenous communications could be divided into three groups [16].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal venous macroaneurysms, typically originating from the capillary bed, are rare and have been described in Coats disease and following branch retinal vein occlusion. 4,5 Previous reports have documented macroaneurysms occuring in eyes with retinal macrovessels 6,7 , although none have used multimodal imaging including optical coherence tomography angiography (OCTA) to aid in the diagnosis, management and follow-up of these vascular abnormalities.…”
Section: Introductionmentioning
confidence: 99%